Mobilization for violent politicized Islam: motivations of former participants in al-Shabaab - Zitzmann, Hawa Noor (Political violence, 2025)
This book focuses on the involvement of some Kenyans in al-Shabaab, an affiliate of Al-Qaeda based in Somalia, despite their country's relative stability compared to Somalia. The book discusses the origin of the Kenyan state and how colonization created social stratification that benefited elites closer to the centre, while excluding marginalized groups at the periphery. The argument is that this pattern still prevails, despite attempts to enhance equality, such as the adoption of a new constitution in 2010 promoting the devolution of power and resources. The persistence of this condition, it is argued, is what initially handed al-Qaeda and later al-Shabaab opportunities for mobilization, enabled by its creative politicization of religion. The heavy-handed tactics employed by security forces under the auspices of the 'War on Terror' further catalysed this process, resulting in more Kenyan individuals joining the group. Using an historical and political process approach, the book shows how the interplay of structural conditions and al-Shabaab's mobilization strategy linked with individuals' motivations for joining the group. Based on individuals' own narratives about their participation, the latter is empirically demonstrated to be non-linear, incorporating motivations beyond rational ones, contrary to the overemphasis on ideology in the literature on participation in groups similar to al-Shabaab.